Where’s He Going?: Mark 6:45–52 - Blount, Brian K. (Interpretation, 2025)
A sermon preached by the Rev. Dr. Brian K. Blount on the occasion of Union Presbyterian Seminary’s graduation ceremony on May 27, 2023, in Richmond, Virginia, the year of his retirement as President of the seminary.